Prototipos arquitectónicos para el avistamiento científico de las especies de aves (residentes, endémicas y migratorias), en el territorio Ramsar de La Laguna de Sonso. (2022)
The Alto Río Cauca Humedales complex, associated with the Sonso or Chircal Lagoon, cataloged worldwide as a RAMSAR site, is of singular ecological value due to several factors, its landscape, diversity of flora and fauna, its high ecotourism potential, recreational and bird watching.